2016
DOI: 10.1111/apa.13657
|View full text |Cite
|
Sign up to set email alerts
|

Sleep differences in one‐year‐old children were related to obesity risks based on their parents’ weight according to baseline longitudinal study data

Abstract: Sleep differed between one-year-old children with high or low obesity risks, based on their parents' body mass index, and was associated with the family obesity risk and parental sleep. The child's bedtime was weakly associated with their weight status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
(42 reference statements)
2
5
0
Order By: Relevance
“…Family and parental factors, such as low socio‐economic status, emotion disorders and high involvement during child sleep, have been associated with poor sleep and more sleep problems in children . The association between child and parental sleep quality has also been observed previously . Our finding added that family high obesity risk, based on parental weight, was probably also related to child poor sleep characteristics.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Family and parental factors, such as low socio‐economic status, emotion disorders and high involvement during child sleep, have been associated with poor sleep and more sleep problems in children . The association between child and parental sleep quality has also been observed previously . Our finding added that family high obesity risk, based on parental weight, was probably also related to child poor sleep characteristics.…”
Section: Discussionsupporting
confidence: 83%
“…21,22 The association between child and parental sleep quality has also been observed previously. 23,24 Our finding added that family high obesity risk, based on parental weight, was probably also related to child poor sleep characteristics. Given the association between poor sleep and unhealthy weight development, 3 the prevalent unfavourable sleep characteristics in children with obese parents may also contribute to the transfer of adiposity through generations in these high-risk families.…”
Section: Discussionmentioning
confidence: 67%
“…This finding is not consistent with our previous observations among children age 1 to 2 years, in which long sleep latency, low sleep efficiency, as well as variable sleep schedules between weekdays and weekends were more common in children at high obesity risk. 15,24 We hypothesized that children in families with obese parents were more exposed to unfavorable sleep hygiene because it has been reported that adults with obesity tend to have poorer and more irregular sleep than normal-weight individuals. 25,26 However, we could not confirm this hypothesis in the follow-up data using objective measures.…”
Section: Discussionmentioning
confidence: 99%
“…Their research also demonstrated that increased sleepiness and decreased performance occurred despite SWS preservation in terms of absolute amounts or increase as a percentage of total sleep 49 . Ekstedt et al further linked microarousals with elevated levels of cortisol, lipids, heart rate, and blood pressure, as well as self-reported work-related stress, showing possible metabolic and cardiovascular contributions50,51 . Roman et al found chronic sleep restriction may lead to changes in neurotransmitter receptor systems and neuroendocrine reactivity in a manner similar to that seen in depression, that's means chronic stress and sleep loss may partly via different pathways, change the brain into a direction as it is seen in mood disorders52 .…”
mentioning
confidence: 99%